Desenvolvimento fisiológico e conservação pós-colheita de jabuticaba - Garcia, Lismaíra Gonçalves Caixeta (2017)
Jabuticaba fruit is known and appreciated all over the world. Despite its recognized functional properties, it has a limited market due to its high perishability. The present study aimed to evaluate the physicochemical characterization of jabuticaba fruits variety Pingo de mel during its physiological development, and the effect of different calcium chloride concentrations on the post-harvest conservation of jabuticaba at different storage temperatures. To evaluate the physiological development, the fruits were collected ten days after the anthesis (DAA) until complete maturation, with intervals of four days between the collections. The period between anthesis and maturation was 34 days. For the post-harvest analysis, the fruits were collected 30 days after the anthesis and immersed into calcium chloride solution at different concentrations (0%, 2%, 4%, and 6%) for 30 minutes at room temperature. Then, the fruits were dried and packed in polypropylene bags and stored at different temperatures (6°C, 12°C, and 25°C). Samples were analyzed at time 0 and every two days, up to 12 days of storage. In the physiological development, the mean diameter, mass, soluble solids, and anthocyanins content increased up to 30 DAA, while the soluble pectin increased up to 34 DAA. A reduction in respiratory rate was observed up to 30 DAA, as well as the firmness and total chlorophyll indices up to 34 DAA, and pH up to 18 DAA, which increased up to 34 DAA. In contrast, an opposite behavior was observed for acidity values. Higher levels of phenolic compounds, hydrolyzed tannins, and antioxidant activity were observed at 10 DAA, while the vitamin C content was higher throughout the maturation stage. An increase in moisture, protein, and lipids was observed up to 18 DAA, with reduction until maturation, with opposite behavior for ash and carbohydrates levels. In general, minerals decreased throughout the development stage. In relation to the carbohydrate profile, higher fructose contents were observed with an increase during maturation. In the post-harvest evaluation, the different calcium chloride concentrations had no effect on the maintenance of fruit characteristics over time, at different storage temperatures. Throughout the storage, there was an increase in pectin, antioxidant activity, CO2, total sugars, acidity, and mass loss. Higher storage temperatures affected both the increase in mass loss, pH, and O2 production, and the reduction of vitamin C content Therefore, to obtain better quality fruits concerning the degree of maturation, it is of great importance to harvest jabuticaba between 30 and 34 DAA. Refrigeration was important for the post-harvest conservation of the jabuticaba fruits variety Pingo de mel, once the fruits stored at 6 ° C suffered minor variations, with improvements or little changes during the 12 days.